New alien in town: first record of Parakontikia ventrolineata (Platyhelminthes: Geoplanidae) in Italy - Mori, Emiliano; Romiti, Federico; Magliano, Adele; Liberato, Claudio De; Ancillotto, Leonardo (Zootaxa, 2024)
\